Romantisisme pada Karya-Karya Raden Saleh: Suatu Tinjauan Kritik Seni - Annisa Desmiati; Yustiono Yustiono; Agung Hujatnika (Journal of Visual Art and Design, 2013)
Raden Saleh is a 19th century Indonesian painter who had the opportunity to master the European paintings in his time. He was born in Terbaya, Semarang on 1807 from a noble family. He then studied painting under the Belgian painter A.A.J. Payen who was assigned by Dutch colonial ruler to capture Indonesian scenery. After studied for some times in Indonesia, he began to travel to Netherlands, Germany, France, and several other European countries and chiseled his name as a famous Romantic painter both in Europe and in Indonesia. This research began from a predicament on how far Romanticism has its influence on Raden Saleh"Ÿs paintings. Romanticism in Raden Saleh"Ÿs works not only characterized by the visual and themes, but also embedded in Raden Saleh"Ÿs ideas and attitude. Raden Saleh, at that time, developed a distinctive style and themes under the Romantic spirit which is mostly a depiction about hunting scenes, allegorical landscape, and dramatic scenes that involves human"Ÿs emotion. Nevertheless the influence of Romanticism is to be found more on Raden Saleh"Ÿs ideas and attitude, such as the idea about the grandeur of nature, exoticism, orientalism, individual freedom, and struggle for liberty.